A well-defined nitro-functionalized aromatic framework (NO2-PAF-1) with high CO2 adsorption: synthesis via the copper-mediated Ullmann homo-coupling polymerization of a nitro-containing monomer. Issue 4 (8th December 2015) - Hei, Ze-Huan; Huang, Mu-Hua; Luo, Yunjun; Wang, Yingxiong
Abstract : A nitro group functionalized porous aromatic framework (NO2 -PAF-1) was synthesized via a copper-mediated Ullmann reaction. Its CO2 uptake was higher that of PAF-1 due to the strong interaction of the nitro group with CO2 . Abstract : A well-defined nitro group functionalized porous aromatic framework (NO2 -PAF-1) was synthesized via a bottom-up strategy using a copper-mediated Ullmann reaction. The synthetic route is cost-efficient and robust for large scale preparation. The Brunauer–Emmett–Teller (BET) specific surface area of the obtained NO2 -PAF-1 is up to 610 cm 2 g −1 with micro/mesoporosity. Its CO2 uptake was measured to be higher than that of PAF-1 due to the strong interaction between the nitro groups and CO2 molecules, proven by the enhanced isosteric heat of CO2 adsorption (38.4 kJ mol −1 ).